Evaluation of teaching–learning methods and mentoring in pharmacology among second-year MBBS students: A cross-sectional study. - Pentareddy, Dr. Mary Rohini; Baguruballi, Dr. Roopa; Merugu, Dr. Padma Latha; Sayana, Dr. Suresh Babu (Student’s Journal of Health Research Africa, 2025)
Background: Pharmacology is a pivotal discipline in medical education, bridging the gap between basic sciences and clinical practice. As the subject continues to evolve with rapid drug development and therapeutic innovations, teaching methodologies must also adapt to ensure effective student learning. Several educational reforms have been proposed and implemented in recent years, yet understanding students’ perspectives remains crucial for identifying gaps and improving pedagogical strategies. Objectives: The present study aimed to assess undergraduate medical students’ perceptions of pharmacology and to obtain structured feedback on the effectiveness of current teaching and learning methods. Methods: A cross-sectional study was carried out among 150 undergraduate medical students after obtaining approval from the Institutional Ethics Committee. A prevalidated questionnaire covering various aspects of pharmacology teaching was administered to the participants following informed consent. Responses were systematically collected, compiled, and analyzed. Results: Out of 150 students approached, 129 completed the survey (response rate: 86%). The majority were females (64.3%), with an age range of 18–22 years (mean ± SD: 19.8 ± 0.9 years). Most respondents hailed from urban backgrounds (58%) and were hostel residents (62%). Central nervous system pharmacology was perceived as the most interesting topic (35.7%), followed by cardiovascular and autonomic pharmacology. Regarding teaching preferences, students favored case-based learning (34%) and blackboard teaching (29%), while audiovisual aids and didactic lectures were rated least engaging. A substantial proportion (90.4%) endorsed structured mentoring, preferably by senior faculty members. Conclusion: This study underscores the value of regularly obtaining student feedback to refine and implement effective teaching-learning strategies in pharmacology. Recommendations: Incorporating case-based discussions, interactive activities, digital tools, periodic quizzes, and structured faculty mentoring can significantly enhance pharmacology education and improve long-term knowledge retention.